Higher adherence to the Mediterranean diet is inversely associated with having hypertension: is low salt intake a mediating factor?. (17th February 2018) - La Verde, Melania; Mulè, Serena; Zappalà, Gaetano; Privitera, Gaetano; Maugeri, Giuseppe; Pecora, Francesco; Marranzano, Marina
Abstract: Blood pressure (BP) is a major risk factor for population health worldwide and a preventable disease through lifestyle modification. The aim of this study was to assess the association between adherence to the Mediterranean diet (MD) and occurrence of hypertension in a Mediterranean cohort. Demographic and dietary data of 1937 adults were collected in 2014–2015 from the general population of Catania, Sicily (Italy). Food frequency questionnaires and a MD adherence score were used to assess exposure variables. Higher adherence to the MD was inversely associated with hypertension. However, this association was no more significant after adjustment for sodium and potassium intake. These results suggest that salt may exert a mediating effect of high adherence to the MD towards hypertension.